Comparative Study of Cognitive Bias and Mental Imaging Modifications on Verbal Memory and Vision of Students - Ashab Sohof, Maryam; Razavi Nematollahi, Vida Sadat; Tajrobehkar, Mahshid; Zeinoddiny Meimand, Zahra (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The present study was carried out with the aim of a comparative study of cognitive bias adjustment training and mental imagery on the verbal and visual memory of female students of the first year of high school. Methods: The present study was designed and implemented as an experimental study with a pre-test and post-test design and with a control group. Subjects were randomly replaced in two experimental groups and one control group. The data was obtained using the Wechsler memory test, which was performed individually. Then, the group of cognitive bias adjustment sessions and Simonton's guided mental imagery (Karami & Moradi, 2009) were exposed to different trainings during 8 90-minute sessions, while the control group remained without any intervention. After the training of the experimental groups, the Wechsler test was again performed on the 3 groups. The data were analyzed using repeated measure analysis of variance, Bonferroni post hoc test and SPSS23 software. Results: The results showed that the effect of cognitive bias adjustment training and mental imagery on verbal and visual memory is positive and significant, and according to the significance level of this test (p=0.699), it can be concluded that there is a difference between the effect of cognitive bias adjustment training and mental imagery on memory. There is no significant difference between students verbally and visually. Conclusion: Teaching different ways of learning in students will have a significant contribution to their school progress due to the greater sensitivity to this segment of the society.